2019
DOI: 10.3390/app9040796
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Methodology to Analyze the Morphological Parameters in Newly Created Tidal Channels Through a Video Monitoring System

Abstract: A video monitoring system has been used in order to track the morphology of an estuary located in La Rabia, due to the high time-space resolution provided by this system. Moreover, the data collection infrastructure allows us to extract relevant information at a relatively low cost. The methodology used to make the image capture and its post-processing procedure, permitted the detection and monitoring of a new tidal channel appearance as well as its evolution in width until it achieved equilibrium. During the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…As a transmission medium, tidal creeks can effectively promote the diffusion of salt marsh vegetation seeds and the saline and freshwater interactions within the tidal creek network regulate the spatial distribution and survival rate of salt marsh plants [6]. The morphological characteristics of tidal creeks are obviously different under the influence of hydrodynamics and anthropogenic activities [7]. Vijay et al [8] revealed that the creek width was reduced due to urbanization.…”
Section: Introductionmentioning
confidence: 99%
“…As a transmission medium, tidal creeks can effectively promote the diffusion of salt marsh vegetation seeds and the saline and freshwater interactions within the tidal creek network regulate the spatial distribution and survival rate of salt marsh plants [6]. The morphological characteristics of tidal creeks are obviously different under the influence of hydrodynamics and anthropogenic activities [7]. Vijay et al [8] revealed that the creek width was reduced due to urbanization.…”
Section: Introductionmentioning
confidence: 99%
“…Tidal creeks are one of the most important geomorphological features of tidal flats, especially in the intertidal zone, and they are substantially affected by hydrodynamic forces and anthropogenic activities [1][2][3]. They are major conduits for the transport of water and sand to the upper part of tidal flats [4,5], and they are also the most active micro-geomorphological unit in the zone of the land-sea interaction [6].…”
Section: Introductionmentioning
confidence: 99%